2018
DOI: 10.1177/2309499018757572
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of arthroscopic capsular release for the diabetic frozen shoulder in Asian patients

Abstract: The diabetic frozen shoulder can be treated favourably with arthroscopic capsular release and the duration of symptoms prior to surgery does not affect the outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…However, at the final follow‐up, there were no significant differences in ROM, except for internal rotation. There is a well‐known correlation between shoulder stiffness and diabetes mellitus [7, 24, 27, 30, 32]. The preoperative ROM in our diabetic patients agreed with these studies; however, whether diabetes is a risk factor for shoulder stiffness after rotator cuff repair is still under debate.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, at the final follow‐up, there were no significant differences in ROM, except for internal rotation. There is a well‐known correlation between shoulder stiffness and diabetes mellitus [7, 24, 27, 30, 32]. The preoperative ROM in our diabetic patients agreed with these studies; however, whether diabetes is a risk factor for shoulder stiffness after rotator cuff repair is still under debate.…”
Section: Discussionsupporting
confidence: 82%
“…Diabetes mellitus can cause a wide variety of musculoskeletal disorders [1], and the shoulder joint is one of the most affected parts of the body [5, 7, 18, 26, 27, 30, 32]. A meta‐analysis has shown that patients with diabetes were 5 times more likely to have frozen shoulder than non‐diabetics [34].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes patients have a higher prevalence of frozen shoulder than the general population and these individuals are less responsive to therapy and have a larger range of motion limitation [15].…”
Section: Introductionmentioning
confidence: 99%